2018
DOI: 10.12988/ces.2018.8272
|View full text |Cite
|
Sign up to set email alerts
|

Effect of alkaline pretreatment on biogas production from corn (Zea mays) crop residues biomass

Abstract: Biogas represents a green energy source that has received major attention as an alternative for fossil fuel depletion. In this work, corn crop residues were used as feedstock for biogas production by anaerobic digestion. The effect of alkaline pretreatment was also evaluated. Proximate analysis was performed to inoculum samples in order to determine volatile and total solids content. Experiments were performed in duplicate varying both parameter particle size (0.5 mm, 1 mm, 2 mm, and in natura) and inoculum to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…The experiment was conducted using a 10-liter digestion device and a 35-week holding period. The volume of gas produced from bananas beels and bananas was about (2409 cm 3 and 8800 cm 3 ). However, the largest amount of biogas was obtained in a digestion device containing equal proportions of banana and banana beels about of 13356cm 3 as feed stocks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The experiment was conducted using a 10-liter digestion device and a 35-week holding period. The volume of gas produced from bananas beels and bananas was about (2409 cm 3 and 8800 cm 3 ). However, the largest amount of biogas was obtained in a digestion device containing equal proportions of banana and banana beels about of 13356cm 3 as feed stocks.…”
Section: Introductionmentioning
confidence: 99%
“…Based on this research finding, the optimum design and condition is found for 2-stages digestion where TSS = 4% and 1 bar, with temperature at first and second digester is 60oC and 42oC, respectively, which produces 7,725 kg/day biogas. The optimum methane purification is found in 5-stage scrubber at 10 bars, with water discharge of 11,000 kg/hr, which produces 7,627 kg/hour CH4 with 97.24% methane content [3]. Represented a biogas source of green energy that is of great interest as an alternative to the depletion of fossil fuel.…”
Section: Introductionmentioning
confidence: 99%